The role of new varieties and chemical fertilizer under risk: The case of smallholders in Eastern Oromia, Ethiopia. - Emana, B. (University of Hannover, 2000)
During 1996-1997, a survey was conducted among 148 farm households in Babile, eastern Oromia, Ethiopia, to estimate the benefits of adopting new varieties of maize and sorghum and of chemical fertilizers. The adoption behaviour of the farm households was analysed and determinants of innovation adoption were identified. The state of household food security was evaluated in terms of risk and various coping mechanisms were described. The stochastic household income was estimated by defining the distribution of the stochastic elements of household income. It was found that under risk the contribution of the new technologies to household food security was only moderate. It was apparent that the current package of agricultural technologies was not the best option for overcoming the problem of food insecurity in Babile. A number of alternative approaches is suggested, including strengthening of agricultural extension, new credit schemes, and crop insurance. KEYWORDS: TROPAG | Zea mays | Sorghum bicolor | innovation adoption | farm surveys | food crops | varieties | inorganic fertilizers | climate | risk | food security | Ethiopia | Oromiya.